PENYELESAIAN TRAVELING SALESMAN PROBLEM PADA PERUSAHAAN DISTRIBUSI PRODUK DENGAN ALGORITMA FARTHEST INSERTION - Lisnawanty Lisnawanty (Universitas Bina Sarana Informatika, 2016)
A Company is an organization that has a complexity of problems in managing the relationship between retailers and distributors to keep the process running smoothly distributing products. The problems that often occur in the distribution company is to determine the best route for delivering products to a number of retailers that will be visited. In the case of Traveling Salesman Problem, this study made some observations on Yakult Company in Pontianak. Based on observations, it is known that the distribution system is done simply. In other words, there is no strategy developed to make the process of distribution, so that in one distribution process not all retailers can be visited. This study discusses the Traveling Salesman Problem solving problems in product distribution company. The method used is the method of heuristic algorithms using Farthest Insertion.Keywords: Traveling Salesman Problem, farthest insertion, retailers, distribution